“Bad boys don't cry”: a thematic analysis of interpersonal dynamics in interview narratives of young offenders with psychopathic traits - De Ganck, Julie; Vanheule, Stijn (Frontiers in Psychology, 2015)
Most discussions of the social and interpersonal styles in individuals with strong psychopathic traits focus on their dangerousness or their affective and interpersonal deficiencies. This study has a different focus, and starts from the idea that such focus on the threat emanating from individuals with a psychopathic style might blind us from the logic inherent to their way of relating with the world. By means of a qualitative analysis (thematic analysis) of narratives from a Lacanian talking therapy, this study examines how 15 youngsters with strong psychopathic traits make sense of interpersonal events and relations. The main recurring theme across these narratives was that others in general are fundamentally distrustful antagonists that they have to protect themselves from. Especially the father figure, with whom identification seems to take place, is seen as a violent actor. Consequently, these youngsters develop multiple strategies of dealing with the threat they experience in relation to (significant) others. These relationship patterns also emerged within the therapeutic relationship, resulting in frequent testing of the therapist’s trustworthiness. The results of this study, discussed in terms of Lacanian theory, might help therapists to develop treatment approaches that better fit with the interpersonal orientation of individuals with strong psychopathic traits.